Initiating DNA barcoding of Eastern Mediterranean deep-sea biota - PAZ, GUY; YUDKOVSKY, YANA; SHAISH, LEE; STERN, NIR; LUBINEVSKI, HADAS; MIENIS, HENK K; DOUEK, JACOB; GALIL, BELLA S; GOREN, MENACHEM; RINKEVICH, BARUCH (Mediterranean Marine Science, 2019)
Preliminary results of DNA barcoding survey of deep-sea mega-faunal biota are presented, collected by trawl and gillnet off the Israeli coast (SE Mediterranean, depths 700 to 1500 meters) during 2012-2013. 846 organisms were identified to 37 species, mainly fish and decapod crustaceans. The most abundant species were the blackmouth catshark Galeus melastomus, the cosmopolitan decapod Polycheles typhlops and the bivalve Abra longicallus. Two species were sampled for the first time from the southern Levant- the long armed chiroteuthid squid Chiroteuthis veranyi and the common mora, Mora moro. Four of the 18 fish species and two of the 10 crustacean species were abundant, representing 78% and 61%, respectively, of the organisms collected. Most other species are represented by fewer than 10 individuals. PCR products for the cytochrome c oxidase sub unit I (COI) gene for the 37 species were successfully sequenced. The identified and vouchered individuals are stored at the Steinhardt Museum of Natural History (Tel Aviv University, Israel) and their COI sequences were uploaded into the BoLD universal data center as part of the national marine barcoding project. The COI sequences of Acanthephyra eximia, Gryphus vitreus, Galeodea echinophora, Mesothuria intestinalis and Astropecten irregularis, constitute first records of these species in BoLD. When compared to the COI sequences in BoLD, the present results reveal some inconsistency in species identification, an outcome that should be taken into consideration primarily once the taxonomical verifications of collected taxa are elusive. This study is the first step in DNA barcoding of the Levant’s little-known benthic deep-sea fauna.